Agrometeorological evaluation of mustard (Brassica juncea) under organic production in North Western Indo-Gangetic Plains - JAT, N K; SHAMIM, M; KUMAR, SUDHIR; RAVISANKAR, N; YADAV, R S; BABU, SUBHASH; PANWAR, A S (The Indian Journal of Agricultural Sciences, 2022)
A field experiment was conducted to evaluate agrometeorological parameters associated with seed yield of Indian mustard (Brassica juncea L.) varieties in an organic production system. During the study, significant variation was recorded in crop phenophases, growth, yield attributes, and seed yield of mustard. Varieties NRCHB-101 and Pusa Mustard-25 have taken significantly minimum days to commence flowering (46–48 days) and attaining physiological maturity (89–90 days). Variety RGN-48 being at par with RH-406 and RGN-229, recorded significantly higher plant height, while RGN-229 recorded the significantly highest biomass accumulation at all the growth stages. Varieties RH-406, Pusa Bold, and DRMRIJ-31 recorded significantly higher seeds per siliqua (16.2–16.5), whereas significantly higher test weight was recorded in Pusa Bold (6.3 g) and DRMRIJ-31 (6.0 g). In seed yield, variety RH-406 (1.97 t/ha) and DRMRIJ-31 (1.42 t/ha) were found significantly highest and lowest, respectively. A significant positive correlations of mustard seed yield was noticed with biomass accumulation at 30 DAS (r=441**), 60 DAS (r=0.614**), 90 DAS (r=0.620**) and biological yield at harvest (r=0.496**). Contrary to test weight, seeds per siliqua had shown a positive effect (r=0.266*) on the seed yield of the mustard. Seed yield of mustard was also influenced by some agrometeorological indices with correlation coefficients (r) of mean minimum temperature at flowering and physiological maturity and mean maximum temperature at physiological maturity were -0.207*, -0.249*, and -0.241*, respectively. Net solar radiation and cumulative temperature difference at physiological maturity also had significant and positive effects on the seed yield of mustard.